Microtus middendorffi - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Microtus middendorffi (Poliakov, 1881). Mem. Acad. Imp. Sci. St. Petersbourg, 39:70. TYPE LOCALITY: Russia, Krasnoyarsk Krai, Taimyr Peninsula. DISTRIBUTION: NC Siberia, from the Polar Ural Mtns to the N Lena River region, south in Urals to 62°N, and in the Lena Valley near Yakutsk. SYNONYMS: obscurus, ryphaeus, swerevi, tasensis, uralensis. COMMENTS: Subgenus Alexandromys, middendorffi species group sensu Zagorodnyuk (1990). Meier (1983) considered M. middendorffi to be phylogenetically distant from other northern and central Asian species of Microtus. Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 524, DOI: 10.5281/zenodo.7353098